Crise do processo coletivo brasileiro: papel do ministério público e as sentenças materialmente complexas contra a administração pública - Gonçalves, Samuel Alvarenga (2018)
The purpose of this dissertation is to investigate some shortcomings and deficiencies involving the Brazilian procedural system of compliance and enforcement of judgments handed down in class actions that establish certain obligations to do before the Public Authorities, especially those dealing with the implementation of policies through the realization of diverse social rights. Moreover, it also intends to present some critical considerations about the ineffectiveness of some judicial measures that are traditionally applied in the face of the Executive Branch for the fulfillment of the order, which represents an authentic crisis of collective judicial protection. The premature and disorganized activation of the Judiciary by the various entities legitimized in the collective tutelage weakens the system of delivery of social rights foreseen in the Constitution. It is necessary the formal and pragmatic knowledge of the administrative activity to work on the public policy issue in the area of access to Justice. In fact, the political-administrative world is the area where the Executive Branch carries out its final activities in accordance with the constitutional panel provided for in the Charter of 1988. However, this political-administrative world has very peculiar specificities that end up representing (albeit involuntarily) authentic shields to the jurisdictional invests emanating from the legal world. Therefore, the Law operator must have the sensitivity to realize that sometimes there will be a real administrative encapsulation of the public entity, culminating in constitutional ditches in terms of non-implementation of the social rights envisaged. In the end, as one of the possible solutions to the procedural crisis in complying with complex sentences in the face of the public manager, who is either weak or unfit, this paper intends to suggest its removal due to the application of what we call breach of trust in the mandate theory, a differentiated kind of subrogation applicable to the collective process. In closing to this dissertation, it is to be concluded that there is still a marked legislative and jurisprudential lacuna to address the issue involving the resistance of the Brazilian public manager to comply with sentences handed down in collective actions